Health Benefits and Physiological Effects of Cold Water Immersion: A Review of Current Research - Ossowska, Weronika; Wojdat-Krupa, Karolina; Czarnota, Maksymilian; Monika Rogowska; Płudowska, Klaudia; Ösztreicher , Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Cold Water Immersion (CWI) has become an increasingly popular method of recovery among athletes and individuals seeking physical and mental health benefits. The purpose of this review is to summarize current scientific findings regarding the physiological mechanisms and therapeutic potential of CWI in various populations. State of Knowledge: CWI triggers a range of physiological responses, including vasoconstriction, vasodilation, and activation of the sympathetic nervous system, leading to increased cortisol and adrenaline secretion. These processes may reduce muscle soreness, promote recovery, and enhance circulation. Regular cold exposure has also been linked to improved insulin sensitivity, immune modulation, and increased activity of brown adipose tissue. Moreover, emerging evidence suggests CWI may positively affect mood, reduce symptoms of depression and anxiety, and improve cognitive performance through neuroendocrine and thermoregulatory pathways. However, outcomes vary based on individual characteristics such as age, body composition, and cold tolerance. Risks include hypothermia, arrhythmias, and cardiovascular stress, particularly in susceptible individuals. Conclusion: CWI presents promising physical and psychological benefits but should be approached with caution and individual adaptation. More standardized protocols and long-term studies are needed to confirm its safety and efficacy in diverse populations.